Pharmacokinetics, bioavailability, and plasma protein binding study of glytrexate, a novel multitarget antifolate - Xiang, Jiahong; Wu, Mengqi; Wang, Jianchao; Lin, Mengmeng; Sun, Mengmeng; Li, Xin; Xing, Ruijuan; Guo, Ran; Gu, Jianmin; Lyu, Tao; Wang, Lei; Shi, Xiaowei (Frontiers in Pharmacology, 2022)
Glytrexate, developed by our team, as a novel multitarget folate antagonist, has inhibitory effects on a variety of cancer cell types, especially KB tumor cells (IC50 0.078 nM), and thus has antitumor drug development prospects. However, its pharmacokinetics and plasma protein binding properties remain unknown. In this study a selective and sensitive liquid chromatography-tandem mass spectrometry (LC‒MS/MS) method was developed and verified to facilitate biological analysis. The bioanalysis method was applied to evaluate the stability, plasma protein binding, and pharmacokinetics of glytrexate. Glytrexate is more stable in human plasma than in rat plasma and in human liver microsomes. The binding of glytrexate to human plasma proteins was higher than that to rat plasma proteins, both of which were less than 30%, suggesting that glytrexate may be at a higher concentration at the pharmacologic target receptor(s) in tissues. Pharmacokinetic characteristics were determined by noncompartmental analysis after administration of single oral (12.5, 25 and 50 mg/kg) and intravenous (2 mg/kg) doses in rats. According to the rat oral pharmacokinetic characteristics, glytrexate had linear dynamics in a dose range of 12.5-50 mg/kg and a poor oral bioavailability of 0.57-1.15%. The investigation revealed that the intravenous half-life, AUC, and Cmax of glytrexate were higher than those of pemetrexed, indicating that glytrexate is more stable in vivo than pemetrexed and that fewer doses are needed with a longer dosage interval. Pemetrexed is generally produced as an injection preparation. This provides ideas for the development of glytrexate formulations. Therefore, glytrexate injection has clinical application prospects compared to oral administration. This study provides a basis for further investigations into the pharmacological effects and clinical uses of glytrexate.